Disability and family in the People's Republic of China: Implementation, benefits, and comparison of two mutual support groups. (March 2013) - McCabe, Helen; McCabe, Karen
Abstract Background The authors and 2 Chinese parents established 2 support groups in China. One group was for parents of children with autism, and the other was for young adults with either mental health issues or intellectual disability, and their parents. The purpose of this study was to examine the meaning and effectiveness of these groups from the parents' perspectives. Method Qualitative interviews and questionnaires were completed by members of the groups, across the first 16 months. Facilitator monthly reports were also analysed. Results Members of both groups found the groups provided a feeling of belonging and a place to interact with similar people. Differences existed relating to perspectives on the purpose of the groups and how families benefited, as well as in participation rates. Suggestions were provided by members. Conclusions Implications of the differences in participation and desires of the parents are considered, including the understanding and perceptions of various disabilities in China.